Nanotechnology-Based Strategies for Berberine Delivery System in Cancer Treatment: Pulling Strings to Keep Berberine in Power - Javed Iqbal, Muhammad; Quispe, Cristina; Javed, Zeeshan; Sadia, Haleema; Qadri, Qamar Raza; Raza, Shahid; Salehi, Bahare; Cruz-Martins, Natália; Abdulwanis Mohamed, Zeinab; Sani Jaafaru, Mohammed; Abdull Razis, Ahmad Faizal; Sharifi-Rad, Javad (Frontiers in Molecular Biosciences, 2021)
Cancer is a multifactorial disease characterized by complex molecular landscape and altered cell pathways that results in an abnormal cell growth. Natural compounds are target-specific and pose a limited cytotoxicity; therefore, can aid in the development of new therapeutic interventions for the treatment of this versatile disease. Berberine is a member of the protoberberine alkaloids family, mainly present in the root, stem and bark of various trees, and has a reputed anticancer activity. Nonetheless, the limited bioavailability and low absorption rate are the two major hindrances following berberine administration. Nanotechnology-based therapeutic approaches have been implemented to overcome such problems, ultimately promoting a higher efficacy in the treatment of a plethora of diseases. This review present and critically discusses the anti-proliferative role of berberine and the nanotechnology-based therapeutic strategies used for the nano-scale delivery of berberine. Finally, the current approaches and promising perspectives of latest delivery of this alkaloid are also critically analyzed and discussed.